INNOVATION IN MUSIC - AN EXPECTATION: संगीत में नवाचार - एक अपेक्षा - Joshi, Meenakshi (International Journal of Research -GRANTHAALAYAH, 2015)
In the modern era, the term for the most development or progressiveness is the word 'innovation' which in English language is called pdavanjavavad means something new which can help in development or progress / progress. This newness is more related to technology. Today, the whole world looks determined and committed to this innovation. In the field of education, innovations are being given special place in the continuous efforts being made in the field of studies and teaching. In the field of higher education, the great need for innovations is being realized for special technical arrangements for the use of modern styles of teaching and learning. As a result, innovation, innovation has become an essential requirement for every subject. आधुनिक युग में सर्वाधिक विकास का अथवा प्रगतिषीलता का द्योतक षब्द है ‘नवाचार‘ जिसे अंग्रेजी भाषा में कहते हैं प्ददवअंजपवद अर्थात् कुछ ऐसा नयापन जो विकास अथवा प्रगति/उन्नति में सहायक हो जावे। ये नयापन तकनीकी से अधिक जुड़ा हुआ होता है। आज सारा विष्व इस नवाचार के लिये संकल्पित व कटिबद्ध सा दीखता है। षिक्षा के क्षेत्र में, अध्ययन-अध्यापन के क्षेत्र में निरंतर किये जा रहे सायास प्रयासों में नवाचारों को विषेष स्थान दिया जा रहा है। उच्च षिक्षा के क्षेत्र में अध्ययन-अध्यापन की आधुनिक षैलियों के प्रयोग हेतु विषेष तकनीकी व्यवस्थाओं के लिये नवाचारों की महती आवष्यकता अनुभूत की जा रही है। परिणामतः प्रत्येक विषय के लिये नवाचारों का अन्वेषण, अविष्कार एक अनिवार्य आवष्यकता बन गई है।